Trauma and its impacts on temporal experience : new perspectives from phenomenology and psychoanalysis - Mezzalira, Selene (New York, NY : Routledge, 2022)
"This unique text develops an original theoretical framework for understanding the relationship between trauma and time by combining phenomenological and psychoanalytical traditions. Moving beyond Western psychoanalytical and phenomenological traditions, this volume presents new perspectives on the assessment and treatment of trauma patients. Powerfully illustrating how the temporal dimension of a patient's symptoms has until now been overlooked, the text presents a wealth of research literature to deepen our understanding of how trauma disrupts individual temporal experience. Ultimately, the resulting phenomena that occur (including dissociation and cognitive distortions), positions time as a transdiagnostic psychological dimension, closely connected to the subject's sense of self. This text will benefit researchers, academics, and educators with an interest in psychoanalysis, phenomenology, and trauma and dissociation studies more broadly. Those specifically interested in the philosophy of the mind, Freud, and psychotherapy will also benefit from this book. Selene Mezzalira has completed PhDs in Philosophy (2016) and Clinical Psychology (2018) at the University of Padova, Italy, and Ryokan College, USA respectively. She has been a visiting scholar at Columbia University in the city of New York and at the University of California, Irvine, USA"--
Introduction: Trauma and the Elusive Nature of Psychic Time -- Time and the Nature of Psychological Trauma -- The Concept of Nachträglichkeit and the Traumatic Disruption of Linear Time -- Time, Trauma, and the Unconscious Mind -- Trauma, Time, and Psychopathology -- Dissociation and Traumatic Temporality -- Time, Trauma, and Memory -- Time, Trauma, and Neural (Dis-)Integration -- Time, Trauma, and Therapeutic Change -- Conclusion: Healing from Trauma.
Keywords: Psychic trauma; Time perception; Consciousness; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PHILOSOPHY / Movements / Phenomenology